ANALISIS DESAIN FORMULIR RESUME MEDIS DITINJAU DARI ASPEK FISIK ISI DAN ANATOMI DI UNIT RAWAT INAP UPTD PUSKESMAS KARTASURA - Yustika Ayu Okta; Arifatun Nisaa; Julia Pertiwi (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2020)
The medical resume form is included in the immortalized medical record form and is an important document because it contains a summary of the patient's admission until after the patient goes home. Complete information can make it easier for officers to provide health services to patients and can be used as a basis for consideration in further care for patients. Incomplete filling out inpatient forms can lead to loss of informative function of medical record documents. One of the causes of incomplete form filling is ineffective and efficient form design. The purpose of this study was to analyze the design of the medical resume form at the UPTD Puskesmas Kartasura in terms of anatomy, physical and content aspects. The benefit of this research is that the results of this study can be used as a measure of the extent to which medical record science is applied, especially regarding the analysis of the medical resume form design for inpatients in terms of anatomy, physical, and content aspects. This study used a qualitative research design with a case study approach. This research was conducted in March-April 2020 at the UPTD Puskesmas Kartasura. The research subjects were emergency room doctors, nurses and medical record officers. The object of this research is inpatient medical resume form. Data collection was carried out by observation and interviews. The validation technique of data validity in this qualitative study used triangulation of sources. The results of the study concluded that the medical resume form design was not yet effective and efficient because 100% of the forms were not completely filled. The conclusion in this research is that a new form design is needed by completing the missing form items such as the form edition number and page number, introduction, notes and instructions.